Rapid E. coli detection based on fluorescence technique - Suwan, Supakorn; Phasuk, Kanchana; Chitsakul, Kitiphol; Piyawattanametha, Wibool (My University, 2017)
This research focuses on developing a prototype tool that is portable and develop method to detect Escherichia coli (E. coli) in water by measuring the light of fluorescence from an enzymatic reaction. The procedure can be done easily without need for laboratory professionals within 2 hours. Total coliforms can measure a minimum of at least 10 MPN/mL. This method is an alternative method to determine water quality. It can reduce the shipping water samples step to laboratories, reducing the time to wait for results. And reduces the cost of detecting E. coli, while the efficiency of this method is no different with the Most Probable Number method.
Keywords: Component; formatting; insert; style; styling